Feasibility of eyes open alpha power training for mental enhancement in elite gymnasts - Dekker, M. K. J.; Van den Berg, B. R.; Denissen, A. J. M.; Sitskoorn, M. M.; Van Boxtel, G. J. M. (Journal of Sports Sciences, 2014)
This study focuses on a novel, easy to use and instruction-less method for mental training in athletes. Previous findings suggest that particular mental capacities are needed for achieving peak performance; including attentional control, focus, relaxation and positive affect. Electroencephalography (EEG) alpha brain activity has been associated with neural inhibition during processes of selective attention, for improving efficiency in information processing. Here we hypothesised that eyes open alpha power training by music teaches athletes to (1) learn to self-regulate their brain activity, and (2) learn to increase their baseline alpha power, herewith improving mental capacities such as focusing the allocation of attention. The study was double-blind and placebo-controlled. Twelve elite gymnasts were either given eyes open alpha power training or random beta power training (controls). Results indicate small improvements in sleep quality, mental and physical shape. In our first attempt at getting a grip on mental capacities in athletes, we think this novel training method can be promising. Because gymnastics is one of the most mentally demanding sports, we value even small benefits for the athlete and consider them indicative for future research.